Geostatistics and inverse distance weighing (IDW) multivariate interpolation methods for regional geochemical stream sediment survey for base metal prospecting around Wapsa, Solukhumbu District, Nepal (Journal of Nepal Geological Society, 2023)
A systematic regional geochemical stream sediment survey for base metals copper, lead, and zinc over an area of 200 sq.km was carried out around Wapsa in Solukhumbu District. 200 stream sediment samples were collected from active streams and analyzed them using atomic absorption spectrometry (AAS) method. All chemical analysis data were interpreted with geostatistical analysis and inverse distance weighing (IDW) multivariate interpolation method using the geographical information system (GIS). The results have shown consistency with geology, homogeneity, and mineralization in the area which is verified with significant copper anomaly over an old working area around Wapsa. The log10 transformed data of Cu, Pb, and Zn were used to estimate threshold and anomaly determination. The method is valid for regional geochemical stream sediment surveys for base metals prospecting.